Online event-based conservation documentation: A case study from the IIC website. (2nd January 2016) - Velios, Athanasios
Abstract : There is a wealth of conservation-related resources that are published online on institutional and personal websites. There is value in searching across these websites, but this is currently impossible because the published data do not conform to any universal standard. This paper begins with a review of the types of classifications employed for conservation content in several conservation websites. It continues with an analysis of these classifications and it identifies some of their limitations that are related to the lack of conceptual basis of the classification terms used. The paper then draws parallels with similar problems in other professional fields and investigates the technologies used to resolve them. Solutions developed in the fields of computer science and knowledge organization are then described. The paper continues with the survey of two important resources in cultural heritage: the ICOM-CIDOC-CRM and the Getty vocabularies and it explains how these resources can be combined in the field of conservation documentation to assist the implementation of a common publication framework across different resources. A case study for the proposed implementation is then presented based on recent work on the IIC website. The paper concludes with a summary of the benefits of the recommended approach. An appendix with a selection of classification terms with reasonable coverage for conservation content is included.